Effect of Modulation Format on Signal Strength and Range in CC1101 Wireless Systems - Aji, Purno Tri; Sony, Arya; Prasetyo, Rizky Hidayat; Hendarto, Taufik; Jati, Ahmad Nugroho (Universitas Bandar Lampung (UBL), 2025)
This paper examines the impact of modulation formats on signal strength and communication range in CC1101-based wireless systems. Experiments were conducted with Arduino Nano nodes operating at 433 MHz under line-of-sight (LOS) conditions in a dense built environment. Four modulation schemes OOK/ASK, 4-FSK, MSK, and GFSK were tested with identical parameters, and RSSI values were recorded across increasing distances. Results indicate that 4-FSK provides strong short-range performance, while OOK/ASK achieves more consistent long-range connectivity up to 160 meters. MSK demonstrates stable signal integrity at moderate distances, whereas GFSK shows robustness in interference-prone settings but with limited coverage. The study concludes that modulation scheme selection should be application-specific, balancing trade-offs between range, energy efficiency, and reliability.